Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Find \( f^{-1}(x) \) and identify the domain and range of \( f^{-1} \). As a check, show that \( f\left(f^{-1}(x)\right) = f^{-1}(f(x)) = x \).

Given:
[tex]\[ f(x) = \frac{1}{x^6}, \quad x \ \textgreater \ 0 \][/tex]


Sagot :

To find the inverse of the function \( f(x) = \frac{1}{x^6} \) with \( x > 0 \), we can follow these steps:

### Finding the Inverse Function \( f^{-1}(x) \)

1. Express \( y \) in terms of \( x \):
Given \( y = f(x) = \frac{1}{x^6} \).

2. Swap \( x \) and \( y \):
To find the inverse, we interchange \( x \) and \( y \) to obtain:
[tex]\[ x = \frac{1}{y^6} \][/tex]

3. Solve for \( y \):
Isolate \( y \) by solving:
[tex]\[ y^6 = \frac{1}{x} \][/tex]
Take the sixth root of both sides:
[tex]\[ y = \left( \frac{1}{x} \right)^{\frac{1}{6}} = x^{-\frac{1}{6}} \][/tex]
Thus, the inverse function is:
[tex]\[ f^{-1}(x) = x^{-\frac{1}{6}} \][/tex]

### Domain and Range of \( f^{-1}(x) \)

For the inverse function \( f^{-1}(x) = x^{-\frac{1}{6}} \):

- Domain: The domain of \( f^{-1}(x) \) corresponds to the range of the original function \( f(x) \). Since \( f(x) = \frac{1}{x^6} \) for \( x > 0 \), \( f(x) \) is always positive. Therefore, the domain of \( f^{-1}(x) \) is \( x > 0 \).

- Range: The range of \( f^{-1}(x) \) corresponds to the domain of the original function \( f(x) \). Since the domain of \( f(x) \) is \( x > 0 \), the range of \( f^{-1}(x) \) is also \( y > 0 \).

### Verification of the Inverse Function

To verify that \( f^{-1}(x) \) is indeed the inverse of \( f(x) \), we must show that:
1. \( f(f^{-1}(x)) = x \)
2. \( f^{-1}(f(x)) = x \)

#### 1. Verifying \( f(f^{-1}(x)) = x \):

[tex]\[ f(f^{-1}(x)) = f(x^{-\frac{1}{6}}) = \frac{1}{(x^{-\frac{1}{6}})^6} \][/tex]
Since:
[tex]\[ (x^{-\frac{1}{6}})^6 = x^{-1} *6 = x^{-6/6} = x^{-1} = x^{1} \][/tex]
Thus:
[tex]\[ f(f^{-1}(x)) = \frac{1}{x^{1}} = x \][/tex]

#### 2. Verifying \( f^{-1}(f(x)) = x \):

[tex]\[ f^{-1}(f(x)) = f^{-1}\left( \frac{1}{x^6} \right) = \left( \frac{1}{x^6} \right)^{-\frac{1}{6}} \][/tex]
Which simplifies to:
[tex]\[ \left( \frac{1}{x^6} \right)^{-\frac{1}{6}} = (x^{-6})^{-\frac{1}{6}} = x \][/tex]

Both conditions \( f(f^{-1}(x)) = x \) and \( f^{-1}(f(x)) = x \) are satisfied, confirming that the inverse function is correct.

### Summary

- The inverse function is \( f^{-1}(x) = x^{-\frac{1}{6}} \).
- The domain of \( f^{-1}(x) \) is \( x > 0 \).
- The range of \( f^{-1}(x) \) is \( y > 0 \).

Thus, the solution to the problem is:
[tex]\[ f^{-1}(x) = x^{-\frac{1}{6}}, \quad \text{with domain:} \, x > 0, \quad \text{and range:} \, y > 0. \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.